(untitled) (International Journal of Environmental Sciences, 2025)
Background: In Orthodontics Class II Division I malocclusion with excessive gingival display presents both functional and esthetic challenges. Traditional treatment approaches often involve extractions or surgical intervention with its own limitations. The use of infrazygomatic crest (IZC) implants combined with anterior mini-implants offers a non-extraction, non-surgical alternative for full-arch distalization and anterior intrusion of maxilla. Aim: To evaluate the effectiveness of IZC and anterior mini-implants in achieving total maxillary arch distalization and incisor intrusion, and improvement in smile esthetics in Class II Division I malocclusion patients with gummy smile. Material and Methods: A total of 20 patients aged 15–30 years with Class II Division I malocclusion and ≥2 mm gingival display on smiling were treated using IZC implants (2.0 mm × 12 mm) placed between the upper first and second molars and anterior mini-implants placed between the lateral incisor and canine. Immediate loading was applied using elastomeric chains. Pre- and post-treatment data were analyzed using cephalometric parameters and clinical photographs. Results: Significant improvements were observed in molar distalization (4.6 mm), incisor retraction (4.5 mm), and incisor intrusion (3.6 mm). Overbite was reduced from 7.1 mm to 2.7 mm, and gingival display decreased from 4.4 mm to 0.45 mm. The nasolabial angle increased by 14.1°, indicating enhanced soft tissue profile. No major complications were reported aside from a few cases of minor implant mobility. Conclusion: The combined use of IZC and anterior mini-implants is an effective and minimally invasive technique for managing Class II malocclusion and gummy smile. It provides excellent control over sagittal and vertical tooth movement, reduces treatment time, and delivers significant functional and esthetic improvements without requiring extractions or surgery.